Analysis the Factors of Unemployment Rate in Indonesia on 1990-2022 - Bella Aflahza; Eka Dewi Anggraini; Muhammad Rusdi; Yusnida Yusnida; Benardin Benardin (Fakultas Ekonomi Dan Bisnis, Universitas Bengkulu, 2023)
This study aims to analyze the effects of Domestic Investment, Foreign Investment, inflation and economic growth on the unemployment rate in the Indonesia on 1990 – 2022. This type of research is an quantiatif research, where the analytical tool used is time series data regression analysis which is processed using Stata software. The results of this study found that the variables of Domestic Investment, Foreign Investment, and economic growth had a negative and significant effect on the open unemployment rate in the Indonesia. Meanwhile the variable of inflation had no effect on the unemployment rate in the Indonesia, because in Indonesia was heavy inflation and there outlier data because of a monetary crisis in 1998 and was caused by cost push.